2013
DOI: 10.1002/jcb.24609
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning mesenchymal stem cells with caspase inhibition and hyperoxia prior to hypoxia exposure increases cell proliferation

Abstract: Myocardial infarction is a leading cause of mortality and morbidity worldwide. Occlusion of a coronary artery produces ischemia and myocardial necrosis that leads to left ventricular (LV) remodeling, dysfunction, and heart failure. Stem cell therapy may decrease infarct size and improve LV function; the hypoxic environment, however, following a myocardial infarction may result in apoptosis, which in turn decreases survival of transplanted stem cells. Therefore, the effects of preconditioned mesenchymal stem ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…On the other hand, Karlsen et al showed that hyperoxia of room air was not adverse for the proliferation, differentiation, or phenotype of bone marrow derived MSCs in vitro. Saini et al demonstrated that preconditioned with hyperoxia decreased the apoptosis of MSCs, while increased the the level of survival markers including Akt1, NF‐κB, and Bcl‐2. However, whether hyperoxia will alter the MSC activities via ROS related pathway need to to be further investigated.…”
Section: Surrounding Microenvironments For Regulating Ros Production mentioning
confidence: 99%
“…On the other hand, Karlsen et al showed that hyperoxia of room air was not adverse for the proliferation, differentiation, or phenotype of bone marrow derived MSCs in vitro. Saini et al demonstrated that preconditioned with hyperoxia decreased the apoptosis of MSCs, while increased the the level of survival markers including Akt1, NF‐κB, and Bcl‐2. However, whether hyperoxia will alter the MSC activities via ROS related pathway need to to be further investigated.…”
Section: Surrounding Microenvironments For Regulating Ros Production mentioning
confidence: 99%
“…Saini et al showed hyperoxic and pancaspase pre-treatment of the cells substantially decreased MSC apoptosis in a cardiac infarct model, a scenario that produces an ischemic environment for implanted MSCs. 103 Conversely, Chang et al recently demonstrated the advantages of preconditioning MSCs in hypoxia, which was shown to improve the secretory capabilities of the cells (VEGF, HGF, and others), a main benefit of MSC therapy. 104 Gene therapy in MSCs has also received some attention, as Wang et al recently showed that adenoviral upregulation of protein kinase G1α improved MSC survival following implantation into a similar cardiac infarct model.…”
Section: Promotion Of Msc Survivalmentioning
confidence: 99%
“…), indicating that the inhibitory effect of hyperoxia on cell viability and proliferation is also cell type‐specific. In fact, previous studies have shown that hypoxia exposure decreases proliferation and viability of both human and rat MSCs (Holzwarth et al, ; Saini et al, ), and hyperoxia (100% O 2 ) preconditioning before hypoxia exposure significantly increases the proliferation and survival rates of the rMSCs (Saini et al, ).…”
Section: Discussionmentioning
confidence: 97%